Exploring the transition from student to practitioner in diagnostic radiography. Issue 2 (May 2016) - Naylor, S.; Ferris, C.; Burton, M.
Abstract: Introduction: This study explores the expectations and experiences of newly qualified diagnostic radiographers during their transition into practice. Methods: This was a longitudinal study using interpretative phenomenological analysis methodology. Data were gathered from four students who participated in a focus group. This informed semi structured interviews with a further eight students who were interviewed prior to starting work and three times over the following twelve months. Results: Themes generated from the data included; experience, fitting in, and identity. Conclusion: This study brings to light the experiences of newly qualified diagnostic radiographers. The findings are open to theoretical generalizability and raise issues that may be used by academic staff in the preparation of students and managers who support newly qualified staff members. Highlights: Diagnostic radiographers are well prepared for most clinical practice. Clinical education cannot fully prepare students for the reality of practice. Being familiar with a hospital, and staff, reduces the stress of starting work. Newly qualified radiographers struggle taking responsibility for students. Professional identity is a key issue in the transition from student to practitioner.